PENERAPAN E-GOVERNMENT DALAM MEWUJUDKAN PEMERINTAHAN YANG BAIK DAN BERSIH DI KABUPATEN KATINGAN - Agus Wijaya (Jurusan Ilmu Pemerintahan, 2019)
Seeing the development of the paradigm that has grown in the life of the state since the 1998 reform, it has brought a demand for the creation of clean and good governance in Indonesia. In realizing this, targeted policies are needed, one of which is through the use of Information Technology in the form of e-government. E-Government is the use of information technology by the government in providing options for the public to easily access information in order to increase transparency, accountability, and public participation so that it can be a means of checking and balancing policies and activities carried out by the government. The results of this study indicate that the development of e-government systems in Indonesia in terms of quantity is starting to increase but in terms of quality this is not sufficient. To further improve the development of e-government in Indonesia both in terms of quantity and quality, it is necessary to have a commitment from the government in perfecting e-development. government, especially in terms of infrastructure, human resources, applications, regulations and socialization within the government and to the community. If done seriously this can support the successful implementation of e-government and be able to improve the quality of public services for the creation of clean and good governance in Indonesia.